Nursing Home and Elderly Care Rehabilitation Centres Health Workers' Workload Levels: Individual Workload Perception Scale Turkish Validity and Reliability Study - Fatma Azizoglu; Osman Hayran; Banu Terzi (Atatürk University, 2021)
Aim: The aim of this study is to test the validity and reliability of the individual workload perception scale adapted to Turkish so that nursing home and elderly care rehabilitation centers can use it as a measurement tool to evaluate the workload perception levels of health workers. Method: This methodological study is carried out with the participation of 777 healthcare professionals employed in 47 Nursing Homes and Elderly Care and Rehabilitation Centers located in 10 districts of Istanbul determined by judgmental sampling method over the period January 1, 2020 - March 31, 2020. Study data were collected using the Turkish version of "Personal Information Form" and "Individual Workload Perception Scale" adapted into the Turkish language in determining the reliability of the scale, confirmatory factor analysis is performed to test the validity of Cronbach's alpha coefficient. Results: Cronbach's alpha reliability coefficient of the Individual Workload Perception Scale is calculated as 0.894. As a result of confirmatory factor analysis, the factor structure consisting of 31 items and 5 factors is confirmed and the fit criterion is determined to be within an acceptable level of 0.069. Conclusion: In this study, it is concluded that the scale is a valid and reliable measurement tool that can be utilized in investigating the individual workload perceptions of healthcare professionals employed in nursing homes and rehabilitation centers.